High-speed, FPGA-based photon-counting fluorometer with high data-gathering efficiency. (14th June 2017) - Iwata, Tetsuo; Mizuno, Takahiko
Abstract: We have developed a low-cost, high-efficiency fluorometer using a field-programmable gate array and simultaneous detection of photoelectron pulse trains. The fluorometer covers a time span of 64 ns with a resolution of 1.0 ns/channel. Depending on the number of channels, the signal-gathering efficiency was improved by a factor of 100 relative to that of conventional time-correlated single-photon counting. This assumes that the fluorescence intensity is moderately high but still requires photon counting. The dead time for building a histogram has been reduced to zero, which means that the upper limit of the repetitive excitation frequency could exceed that determined by the time span. We describe instrumental details and demonstrate the basic performance.